2014
DOI: 10.4236/oalib.1100712
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Acid Red 66 Dye from Aqueous Solution by Green Microalgae <i>Acutodesmus obliquus</i> Strain PSV2 Isolated from an Industrial Polluted Site

Abstract: In the present study, Acutodesmus obliquus strain PSV2 was isolated from a textile and dyeing industrial site and investigated as a cost effective and potential adsorbent for Acid red 66 dye. Batch kinetic experiments were carried out as a function of pH (1.0-6.0), contact time (0-180 min) and initial dye concentration (10-50 mg/L) to determine the decolorization efficiency of microalgae. The maximum adsorption of dye was observed at pH 2.0 during the initial 60 min of contact time. The Langmuir and Freundlich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the same way, Daneshvar et al [152] presented the elimination of malachite green via Cosmarium sp. In a further investigation by Sarwa et al [153] the microalga Acutodesmus obliquus was observed to eliminate acid red 66 azo dye from industrial waste water. In the same way, Chlorella vulgaris was discovered to eliminate Congo red with dye removal rate reached up to 83% at an initial concentration of 5 mg/L as well as 53% at a concentration of 25 mg/L [154].…”
Section: Use Of Algae In Wastewater Treatmentmentioning
confidence: 95%
“…In the same way, Daneshvar et al [152] presented the elimination of malachite green via Cosmarium sp. In a further investigation by Sarwa et al [153] the microalga Acutodesmus obliquus was observed to eliminate acid red 66 azo dye from industrial waste water. In the same way, Chlorella vulgaris was discovered to eliminate Congo red with dye removal rate reached up to 83% at an initial concentration of 5 mg/L as well as 53% at a concentration of 25 mg/L [154].…”
Section: Use Of Algae In Wastewater Treatmentmentioning
confidence: 95%
“…จากการทดลองผั นแปรความเข> มข> นเริ ่ มต> นของสี ย> อมที ่ 20-100 มิ ลลิ กรั มตD อลิ ตร พบวD าความเข> มข> นเริ ่ มต> นของสี ย> อม เทD ากั บ 100 มิ ลลิ กรั มตD อลิ ตร เปg นความเข> มข> นเริ ่ มต> นที ่ เหมาะสมตD อการดู ดซั บสี ย> อมเบเนฟA ก เรด โดยพบวD ามี คD าปริ มาณการดู ดซั บ เทD ากั บ 36.82±0.54 มิ ลลิ กรั มตD อกรั มสาหรD าย ซึ ่ งเปg นคD าปริ มาณการดู ดซั บสู งที ่ สุ ด โดยมี ความแตกตD างอยD างมี นั ยสำคั ญทางสถิ ติ กั บ ทุ กชุ ดการทดลองที ่ เหลื อ (Table 3) ความเข> มข> นเริ ่ มต> นของสี ย> อมที ่ เพิ ่ มขึ ้ นจาก 20 ถึ ง 100 มิ ลลิ กรั มตD อลิ ตร นั ้ นพบวD าเมื ่ อความ เข> มข> นของสี ย> อมเพิ ่ มขึ ้ นจะสD งผลให> มี การดู ดซั บสี ย> อมตD อกรั มของสาหรD ายที ่ เพิ ่ มขึ ้ นเนื ่ องจากเกิ ดแรงผลั ก (repulsive force) ที ่ เกิ ด จากความเข> มข> นเริ ่ มต> นของสี ย> อมที ่ มากจึ งทำให> สี ย> อมมี แรงผลั กกั นเองและทำให> สี ย> อมเข> าใกล> สาหรD ายได> มากขึ ้ น ซึ ่ งจะเปg นการเพิ ่ ม การดู ดซั บสี ย> อมทำให> สาหรD ายสามารถดู ดซั บสี ย> อมจากสารละลายได> ดี (Sarwa et al, 2014) The different superscript letters (a,b,…) in each column are significantly different (p<0.05). (Celekli et al, 2012;Gunasundari et al, 2020;Ozer et al, 2005) 6)…”
Section: ผลของความเขU มขU นเริ ่ มตU นของสารละลายสี ยU อมที ่ เหมาะสม...unclassified
“…ดซั บที ่ เวลาใด ๆ การวั ดปริ มาณสี ยU อมและการวิ เคราะหV ขU อมู ล วั ดปริ มาณสี ย> อมด> วยเครื ่ อง spectrophotometer (Genesys 20 Thermo Spectronic, Thailand) ทำการทดลอง แบบสุ D มตลอด (completely randomized design) โดยในทุ กชุ ดการทดลองทำการทดลอง 4 ซ้ ำ วิ เคราะห7 ความแปรปรวนของ ชุ ดทดลองแบบทางเดี ยว (One-way ANOVA) และเปรี ยบเที ยบคD าเฉลี ่ ยโดยวิ เคราะห7 ข> อมู ลโดย Turkey's Honestly Significant Different (HSD) ที ่ ระดั บความเชื ่ อมั ่ น 95 เปอร7 เซ็ นต7 โดยใช> โปรแกรมสำเร็ จรู ปสำหรั บคอมพิ วเตอร7 SPSS For Windows 16.0 (Ibm spss statistics, 2023) ผลการศึ กษาและวิ จารณj ผลของระดั บพี เอชที ่ เหมาะสมต= อการดู ดซั บสี ยU อม ระดั บพี เอชของสารละลายที ่ เหมาะสมในการดู ดซั บสี ย> อมเบเนฟA ก เรด โดยสาหรD าย N. oculata ที ่ ตรึ งในเม็ ดอั ลจิ เนต โดยพบวD า สาหรD ายดู ดซั บสี ย> อมได> สู งที ่ สุ ดที ่ ระดั บพี เอช 2 โดยมี คD าเปอร7 เซ็ นต7 การดู ดซั บ (removal) เทD ากั บ 89.60±0.64 เปอร7 เซ็ นต7 และมี ปริ มาณสี ย> อมที ่ ถู กดู ดซั บตD อปริ มาณสาหรD าย (adsorption capacity) 0.90±0.01 มิ ลลิ กรั มตD อกรั มสาหรD าย โดยมี ความแตกตD าง อยD างมี นั ยสำคั ญทางสถิ ติ กั บทุ กระดั บพี เอช (Table 1) ซึ ่ งมี รายงานการศึ กษาคล> ายคลึ งกั นในการใช> สาหรD ายสี เขี ยวขนาดเล็ ก Chlorella vulgaris เปg นตั วดู ดซั บทางชี วภาพใน การดู ดซั บสี ย> อมรี แอคที พ (Akzu & Tezer, 2005) เนื ่ องจากสี ย> อมเบเนฟA ก เรด นั ้ นจั ดเปg นสี ที ่ อยู D ในกลุ D มรี แอคที พ เมื ่ อละลายในน้ ำจึ งให> ประจุ ลบจึ งจั บกั บหมู D ฟ" งก7 ชั นที ่ เปg นประจุ บวก เชD น คาร7 บอกซิ ล ไฮดรอก ซิ ล กรดอะมิ โน (Schiewer & Volesky, 2000) บนพื ้ นผิ วของเซลล7 สาหรD าย นอกจากนี ้ ที ่ พี เอชต่ ำสี ย> อมสามารถแตกตั วได> ดี สD งผลให> เกิ ดปฏิ สั มพั นธ7 กั นระหวD างประจุ บวกที ่ อยู D บนพื ้ นผิ วของเซลล7 สาหรD ายกั บประจุ ลบของสี ย> อมกลุ D มรี แอคที พได> มาก เมื ่ อคD าพี เอช เริ ่ มเพิ ่ มขึ ้ นเรื ่ อย ๆจนถึ งพี เอชเทD ากั บ 8 นั ้ น จะมี ปริ มาณของประจุ ลบที ่ เพิ ่ มขึ ้ น (OH -) ซึ ่ งประจุ ลบนี ้ สามารถ แยD งจั บกั บประจุ บวก บนผิ วเซลล7 สาหรD ายทำให> ปริ มาณประจุ บวกที ่ อยู D บนพื ้ นผิ วของเซลล7 สาหรD ายที ่ จะจั บกั บสี ย> อมนั ้ นน> อยลงสD งผลให> การดู ดซั บสี ย> อม ลดลงเมื ่ อพี เอชสู งขึ ้ น(Neag & Roman, 2017;Sarwa et al, 2014) …”
unclassified